ENERGY PROCESSES OF MUCOCILIARY CLEARANCE - Vadim S. Isachenko; Lubov V. Minaeva; Vladimir V. Dvorianchikov; Vasiliy G. Mironov; Ksenia V. Vinichenko; Andrey V. Shafigulin; Iliyan Doykov; Dilyana Vicheva (Peytchinski Publishing, 2019)
The main objective of the paper is to describe in detail the physiology and pathophysiology of the mucociliary transport system. Mucociliary clearance (MCC) is a principal component of the respiratory tract. As an important defence mechanism, it provides the necessary potential for the barrier and immune function of the airway. The paper gives an overview of factors affecting the bioenergetic processes in the ciliated epithelium. It focuses on the study ciliary movement performance, generated by adenosine triphosphate hydrolysis.